Mental health interventions for rural adolescents: a scoping review - den Otter- Moore, Sophia (Global Health: Annual Review, 2019)
It is estimated that less than half of adolescents in rural and remote communities receive the mental health support they need due to barriers including limited access to mental health services and care providers, poorer quality mental healthcare, higher transportation costs to services, and stigma. The purpose of this scoping review is to identify mental health interventions that have been implemented and evaluated in the literature specifically for rural adolescents between ages 10-19. A search of Medline was conducted. Of the 62 included studies, a majority were located in high income countries, focused on problematic substance use, were delivered in schools and through tele-health. The results suggest that while there have been diverse efforts to develop mental health interventions in this population, there are limited efforts to bring more specialized mental health services directly to rural communities, and rather a reliance on task shifting and tele-health for these needs. Finally, there is a need for more intervention research targeting high burden disorders among adolescents like anxiety and mood disorders, and more support for intervention activities in low and middle income countries.